Nanomaterial-Enabled Enhancements in Thylakoid-Based Biofuel Cells - Amit Sarode; Gymama Slaughter (Nanomaterials)
Thylakoid-based photosynthetic biofuel cells (TBFCs) harness the inherent light-driven electron transfer pathways of photosynthesis to enable sustainable solar-to-electrical energy conversion. While TBFCs offer a unique route toward biohybrid energy systems, their practical deployment is hindered by sluggish electron transfer kinetics, unstable redox mediators, and inefficient interfacing between biological and electrode components. This review critically examines recent advances in TBFCs, with a focus on three key surface engineering strategies: (i) incorporation of nanostructured materials to enhance electrode conductivity and surface area; (ii) application of redox mediators to facilitate charge transfer between photosynthetic proteins and electrodes; and (iii) functional exploitation of individual thylakoid components, including Photosystem I (PSI) and Photosystem II (PSII), to augment photogenerated current output. By systematically evaluating current advancements, this review highlights the synergistic role of materials and biological components in advancing TBFC technology and offers insights into next generation biohybrid solar energy systems with enhanced efficiency and scalability.